What do husbands know about neonatal danger signs? A cross-sectional study in Dessie City, Northeast Ethiopia - Asnakew Molla Mekonen; Mastewal Arefaynie; Yawkal Tsega; Amare Zeleke; Endalkachew Mesfin Gebeyehu (BMJ Open)
Objective This study assessed husbands’ knowledge of neonatal danger signs in Dessie City, Northeast Ethiopia, focusing on fathers of infants born within the preceding 6 months (2023).Design Community-based cross-sectional study.Setting Dessie City, Northeast Ethiopia.Participants We systematically selected 613 husbands of postpartum women (sampling period: December 15, 2022,–January 15, 2023).Methods Data were collected via structured questionnaires, entered into EpiData (v4.6) and analysed using SPSS (v26). Binary logistic regression identified factors associated with knowledge; statistical significance was set at p<0.05 in the multivariable analysis.Results Among the 613 respondents, slightly over half (53%, n=325) demonstrated good knowledge of neonatal danger signs. Several factors were significantly associated with higher knowledge levels. Husbands residing in urban areas were nearly seven times more likely to have good knowledge compared with their rural counterparts (adjusted OR (AOR)=6.93; 95% CI, 3.23 to 14.90). Educational attainment also played a critical role: those with primary education or higher had 6.44 times higher odds of good knowledge than those with no formal schooling (95% CI, 1.83 to 22.61). Parity was another predictor, with fathers of 2–4 children showing markedly greater knowledge (AOR=10.39; 95% CI, 4.68 to 23.05) than those with only one child. Most notably, receiving information from health professionals had the strongest association—respondents who accessed such guidance were 11 times more likely to be knowledgeable (AOR=11.05; 95% CI, 5.46 to 22.36).Conclusions Nearly half of the participants lacked adequate knowledge. Thus, integrating targeted health education into maternal and child health programmes could improve awareness and neonatal outcomes.